diff --git a/info/exercises/ex-03-sol.pdf b/info/exercises/ex-03-sol.pdf
index 17e187b47360c3eba545dfd53a01f0b3f7d80b90..d9bfc3def389fa5991449936602744798979eedd 100644
Binary files a/info/exercises/ex-03-sol.pdf and b/info/exercises/ex-03-sol.pdf differ
diff --git a/info/exercises/ex-03.pdf b/info/exercises/ex-03.pdf
index cdaf7ef242c891093edfca9551ae32b0b4cb7d62..5430286f7979c4b6fc1c1eac56f7ac4219eb8217 100644
Binary files a/info/exercises/ex-03.pdf and b/info/exercises/ex-03.pdf differ
diff --git a/info/exercises/src/ex-03/ex/table.tex b/info/exercises/src/ex-03/ex/table.tex
index aa1de12f5b9c57eddc61dabd02be26459569ead9..8f84e38f533e450accc409e77033dec2e84167ec 100644
--- a/info/exercises/src/ex-03/ex/table.tex
+++ b/info/exercises/src/ex-03/ex/table.tex
@@ -76,24 +76,8 @@
     generally called \emph{left recursion elimination}.
 
     Transformed grammar steps (explanation below):
-
-    Left recursion elimination (not LL(1) yet! \(\first(S') = \{(, [\;\}\)):
-    \begin{align*}
-      S &::= S' \mid ()S' \mid [\;]S' \\
-      S' &::= (S)S' \mid [S]S'
-    \end{align*}
-
-    Inline \(S'\) once in \(S ::= S'\):
-    \begin{align*}
-      S &::= (S)S' \mid [S]S' \mid ()S' \mid [\;]S' \\
-      S' &::= (S)S' \mid [S]S' \mid \epsilon
-    \end{align*}
-
-    Finally, left factorize \(S\) to get an LL(1) grammar:
     \begin{align*}
-      S &::= (T_1 \mid [T_2 \\
-      T_1 &::= S)S' \mid ~)S' \\
-      T_2 &::= S]S' \mid ~]S' \\
+      S &::= ()S' \mid [\;]S' \\
       S' &::= (S)S' \mid [S]S' \mid \epsilon
     \end{align*}